Exchange of Information and Data Protection in Cross-border Criminal Proceedings in Europe - Gutiérrez Zarza, Ángeles (Springer, 2015)
In the past 10 years, the Member States of the European Union (EU) have intensified their exchange of information for the purposes of preventing and combating serious cross-border crime, as manifested in three main aspects. Firstly, there is a need to ensure the practical application of innovative principles (availability, mutual recognition) and concepts (Information Management Strategy, European Information Exchange Model) for tackling criminal organisations and networks that threaten the Internal Security of the EU. Secondly, there has been a gradual consolidation of EU agencies and bodies (Eurojust, Europol) aimed at promoting cooperation and dialogue among law enforcement officials and judicial authorities responsible for preventing and combating drug trafficking, trafficking in human beings, child pornography, and other serious trans-national offences.